Maternal Risk Factors for Perinatal Mortality (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Objective: This prospective clinical study was designed on maternal risk factors for perinatal  mortality.Material and Methods: This is cross sectional study conducted in the Department of Obstetrics  & Gynae and Department of pediatrics Sylhet M A G Osmani Medical College Hospital, Sylhet, during the period from 1st July 2008 30th June 2009. Here study population were all fresh & macerated stillborn & early neonatal death cases during the study period. For  convenience sampling total 100 cases were studied for this study during the study period.Results: During this period 8398 deliveries were done & there were 715 perinatal deaths. In Sylhet region neonatal mortality rate is higher (53 /1000 total birth) than our national neonatal  mortality rate (37/1000 total birth) (BDHS, 2007). From this study it was revealed that most  important maternal risk factor for perinatal mortality was pre-eclampsia, eclampsia and obstructed labour.Conclusion: Perinatal mortality rate serves as the most sensitive index of maternal and neonatal care. DOI: http://dx.doi.org/10.3329/bjog.v26i2.13786 Bangladesh J Obstet Gynaecol, 2011; Vol. 26(2) : 86-91